Muscle fibrillin deficiency in Marfan's syndrome myopathy. Issue 5 (1st May 2003) - Behan, W M H; Longman, C; Petty, R K H; Comeglio, P; Child, A H; Boxer, M; Foskett, P; Harriman, D G F
Abstract : Objective: To report a family with Marfan's syndrome in whom a myopathy was associated with respiratory failure; muscle biopsies from affected individuals were examined to determine whether there were abnormalities in fibrillin. Methods: 21 family members underwent detailed clinical examination, including neurological and pulmonary assessment. Muscle biopsies in the most severely affected cases were immunostained using monoclonal antibodies to specific fibrillin components. Genomic DNA from all 21 members was analysed for mutations in the fibrillin gene, FBN1, on 15q21. Results: 13 individuals had a C4621T base change in exon 37 of the FBN1 gene, which in four cases segregated with muscle weakness or evidence of respiratory muscle dysfunction or both. Their muscle biopsies revealed an abnormality in fibrillin immunoreactivity. Conclusions: Abnormalities in fibrillin can be detected in muscle biopsies from patients with Marfan's syndrome who have myopathy. This pedigree, with a point mutation in FBN1, also draws attention to the potential for respiratory failure associated with myopathy.